Administrative Neutrality in the Wake of Trumpism. Issue 9 (October 2021) - Box, Richard C.
"Unprecedented" is a much-overworked word in recent descriptions of U.S. politics, but it is difficult to avoid in reflecting on the past 4 years in public administration. Federal civil servants whose work contradicted Trump administration ideology were sidelined, the administration introduced a new employment category that would seriously weaken civil service protections, and government at all levels now functions in an environment of widespread public belief in conspiracy theories and nonfactual disinformation. The article describes changes in the political context of the work of public professionals and examines effects on the important role characteristic of administrative neutrality.